Evaluation of the thickness of acetabular cartilage by ultrasound in developmental dysplasia of the hip - Hong, Kai; Wan, Jie; Zhao, Ying; Zhang, Chao (Frontiers in Pediatrics, 2024)
Introduction: It has been reported that the cartilaginous roof of acetabulum was thicker in developmental dysplasia of the hip (DDH) than in healthy hip. But limited study focused on the changes of the thickness of acetabular cartilage after follow-up or treatment of DDH. Our goal is to report the thickness of acetabular cartilage before and after treatment of DDH. In borderline hips, the thickness of acetabular cartilage decreased from 3.1 ± .57 mm in the primary evaluation to 2.9 ± .53 mm in the last follow-up scan (P = .01). In dysplastic hips, cartilage thickness decreased from 4.3 ± 1.6 mm in the initial evaluation to 3.5 ± .51 mm after treatment (P = .003). The thickness of acetabular cartilage of dysplastic hips after treatment was still thicker than normal hips (P < .0001).The thickness of acetabular cartilage decreased after follow up or treatment of DDH.Whether or not the still thicker cartilage than normal after treatment in dysplastic hips be considered as an early indicator of residual acetabular dysplasia needs to be further studied.